2000
DOI: 10.1385/jmn:14:1-2:027
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neurotrophins BDNF and NT-3, and Their Receptors in Rat Brain After Administration of Antipsychotic and Psychotrophic Agents

Abstract: We have investigated the potential role of neurotrophic factors in antipsychotic drug action by examining the effects of antipsychotic and psychotropic treatments on the mRNA expression of brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and their receptors, trkB and trkC, respectively, in rat brain. Neither acute nor chronic clozapine treatment significantly affected the expression of these mRNAs in any brain area investigated, except for a decrease in trkB expression in the granule cells of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 43 publications
10
29
0
Order By: Relevance
“…7). These findings are consistent with previous studies reporting no effects of chronic exposure to antipsychotic drugs on the levels of BDNF mRNA and protein or the expression of TrkB mRNA in the rodent frontal cortex (Nibuya et al, 1995;Linden et al, 2000;Takahashi et al, 2000;Lipska et al, 2001) (but see Angelucci et al, 2000;Dawson et al, 2001). The results from animal experiments are also complemented by the findings of reduced levels of both BDNF and TrkB mRNAs in the subjects with schizophrenia who were not receiving antipsychotic medications at the time of death.…”
Section: Discussionsupporting
confidence: 93%
“…7). These findings are consistent with previous studies reporting no effects of chronic exposure to antipsychotic drugs on the levels of BDNF mRNA and protein or the expression of TrkB mRNA in the rodent frontal cortex (Nibuya et al, 1995;Linden et al, 2000;Takahashi et al, 2000;Lipska et al, 2001) (but see Angelucci et al, 2000;Dawson et al, 2001). The results from animal experiments are also complemented by the findings of reduced levels of both BDNF and TrkB mRNAs in the subjects with schizophrenia who were not receiving antipsychotic medications at the time of death.…”
Section: Discussionsupporting
confidence: 93%
“…Although Marvanova et al (2001) showed that the structurally related NMDAR-A memantine produced an increase in BDNF mRNA expression in various brain areas, this effect was assessed after acute administration. Similar increases in BDNF expression have been reported for other NMDAR-A, including MK-801 and ifenprodil after acute administration (Linden et al, 2000;Matsuki et al, 2001;Toyomoto et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Clozapine, an atypical antipsychotic, when administered either acutely or chronically did not change trkB or trkC mRNA levels in the cingulate cortex of rodents, but did cause a reduction in trkB mRNA in the olfactory bulb. 13 In our study, the correlations between lifetime neuroleptic exposure and trkB TK þ mRNA levels did reach statistical significance. Additionally, significant positive correlations between trkC mRNA in small neurons and neuroleptic exposure estimates were detected; this supports an earlier observation in cerebellum 34 , albeit our observation is in cerebral cortex.…”
Section: Discussionmentioning
confidence: 42%
“…11 In so far as our classifications may include both pyramidal (large) and nonpyramidal (small) neurons, our observations suggest that both glutamate and GABA-containing neurons in the normal human brain may have the capacity to directly respond to BDNF by activating intracellular tyrosine phosphorylation and associated signaling systems. Indeed trkB mRNA is found in both neuronal types in rodent brain and BDNF can influence the survival, neurite outgrowth and/or synapse formation of both glutamate [12][13][14] and GABA-containing neurons. [15][16][17][18] Since there is evidence for alterations in both excitatory and inhibitory neurons in cortex of subjects with schizophrenia (for reviews, see Blum and Mann 19 ; Goff and Coyle 20 ), we hypothesized that both large and/or small neurons may be compromised by this BDNF reduction and, in turn, may contain abnormal levels of trkB TK þ mRNA in the DLPFC of patients with schizophrenia as compared to controls.…”
mentioning
confidence: 99%